Tertiary Lymphoid Structures as a Predictive Biomarker of Response to Cancer Immunotherapies - Trüb, Marta; Zippelius, Alfred (Frontiers in Immunology, 2021)
Tertiary lymphoid structures (TLS) are ectopic lymphoid formations which are formed under long-lasting inflammatory conditions, including tumours. TLS are composed predominantly of B cells, T cells and dendritic cells, and display various levels of organisation, from locally concentrated aggregates of immune cells, through clearly defined B cell follicles to mature follicles containing germinal centres. Their presence has been strongly associated with improved survival and clinical outcome upon cancer immunotherapies for patients with solid tumours, indicating potential for TLS to be used as a prognostic and predictive factor. Although signals involved in TLS generation and main cellular components of TLS have been extensively characterized, the exact mechanism by which TLS contribute to the anti-tumour response remain unclear. Here, we summarise the most recent development in our understanding of their role in cancer and in particular in the response to cancer immunotherapy. Deciphering the relationship between B cells and T cells found in TLS is a highly exciting field of investigation, with the potential to lead to novel, B-cell focused immunotherapies.